The Conceptual Model of Role Stress and Job Burnout in Judges: The Moderating Role of Career Calling - Pereira, Sandra Patrícia Marques (2022)
Judges are the central actors in the organization and functioning of the judicial system. Concerns about work efficiency, driven by the European Commission for the Efficiency of Justice, led countries to adopt a set of reforms in line with private sector ideals applied to the public field to better manage their financial and human resources. In the last decades, the Portuguese judicial system has undergone a reform based on New Public Management principles by adopting the new Law on the Organization of the Judiciary System (LOSJ), significantly altering judges’ duties, who beyond their traditional role of applying the law, perform the additional role of court-of-law judge-manager. The objective of this study is to explore the influence of role conflict and role ambiguity in occupational burnout among judges and to analyze the influence of calling orientation as a moderating variable, so as to present a conceptual model of role-stress management among the judiciary. Theoretically, this work contributes to the literature on role-stress management through its introduction of calling moderation, as well as to the literature on the positive influence of calling on burnout. In terms of its practical implications, the work contributes to a reconsideration of the current organizational structure of judicial work.